Oncogenic Role of Long Noncoding RNAMALAT1 in Thyroid Cancer Progression through Regulation of the miR-204/IGF2BP2/m6A-MYC Signaling - Mao Ye; Shu Dong; Haitao Hou; Tao Zhang; Minghai Shen (Elsevier, 2021)
Accumulating studies highlight the role of long noncoding RNAs (lncRNAs)/microRNAs (miRNAs)/messenger RNAs (mRNAs) as important regulatory networks in various human cancers, including thyroid cancer (TC). This study aimed to investigate a novel regulatory network dependent on lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in relation to TC development. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blot were initially employed to detect the expression of MALAT1, insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2), and myelocytomatosis (MYC) in TC cells. Interactions among MALAT1, miR-204, and IGF2BP2 were then identified in vitro. The biological processes of proliferation, migration, invasion, and apoptosis were evaluated in vitro via gain- and loss-of-function experiments, followed by in vivo validation using xenograft mice. Our data indicated that MALAT1 and IGF2BP2 were highly expressed, while miR-204 was poorly expressed in TC. IGF2BP2 was verified as a target of miR-204. MALAT1 was found to upregulate IGF2BP2 and enhance MYC expression via m6A modification recognition by competitively binding to miR-204, conferring a stimulatory effect on proliferation, migration, and invasion of TC cells, which was accompanied by weakened tumor growth and cell apoptosis. Altogether, the central findings of our study suggest that MALAT1 contributes to TC progression through the upregulation of IGF2BP2 by binding to miR-204.